Influence of buccal-lingual width on the survival rate of proximal ART restorations in ponterior teeth - Carolina Guedes Barquete; Antônio Fernando Monnerat; Cesar dos Reis Perez (Associação Brasileira de Odontologia, 2018)
Objective: this study examined the relationship between the buccal-lingual width and the survival rate of multiple surface restorations, after simulated mechanical cycling. Material and Methods: three cavity's widths were evaluated: Regular (R = 3.21mm), Large (L = 4.81mm), and Very Large (VL - 6.42mm). Thirty extracted teeth were selected, prepared, restored with high viscosity glass ionomer cement through the ART technique and subject to simulated mechanical cycling. In each group, the samples were classified according to four different scores: 0 - no fracture, 1 - fracture with no repair needed, 2 - fracture with possible repair, and 3 - complete restoration loss/impossible to repair. Kruskal-Wallis test was used for the analysis of categorical outcomes. Results: there was a significant statistical difference between all groups (p